Rys historiograficzny dekady gierkowskiej. Przyczynek do problematyki polskiego piśmiennictwa historycznego na temat lat 70. XX wieku w Polsce - Domke, Radosław (W kręgu wyobrażeń zbiorowych. Polityka, władza, społeczeństwo, 2019)
In article I amtrying to summarise polish historiography about Gierek’s decade. Since the end of this period only 35 years have passed, but even now we can define some plots on that field. Historical literature upon that thing can be divided into four periods. In some of them we can find more or less critical discourses. The paper help us figure out which was dominant in current period. In that way we can recapitulate how was seen „the decade of accelarated development” in polish historiography, was it a „paradise”, or opposite.